Employing the Dynamics of the Electrochemical Interface in Aqueous Zinc‐Ion Battery Cathodes. (23rd June 2021) - Becknell, Nigel; Lopes, Pietro P.; Hatsukade, Toru; Zhou, Xiuquan; Liu, Yuzi; Fisher, Brandon; Chung, Duck Young; Kanatzidis, Mercouri G.; Markovic, Nenad M.; Tepavcevic, Sanja; Stamenkovic, Vojislav R.
Abstract: Intrinsically stable materials are desirable for constructing energy storage devices, which aim to demonstrate durability under the harsh electrochemical conditions that are detrimental to their lifespan. However, it is demonstrated here that the intrinsic instability of an electrochemical interface can be converted from an obstacle into an advantage. In aqueous zinc‐ion batteries, manganese oxide (MnO2 ) exhibits considerable dissolution even in electrolyte containing Mn 2+ salt. Balancing with redeposition alleviates the harmful impact of dissolution on performance and alters the trajectory of the active phase. Inclusion of Mn 2+ salt in the electrolyte induces MnO2 deposition on all conductive surfaces, requiring that distracting side reactions be eliminated to isolate the dynamics of the active phase. Under conditions favoring dissolution, capacity decreases dramatically and a highly crystalline tetragonal ZnMn2 O4 phase forms, while redeposition helps maintain capacity and promotes a disordered cubic Zn‐rich phase. Ultimately, this work aims to illuminate a path forward to unlock the potential of batteries made with materials that are fundamentally unstable in their operating environment. Abstract : Multiple mechanisms for generating capacity in a zinc/manganese oxide (Zn/MnO2 ) battery are compared. The focus is placed on dissolution and the advantages that it provides fortifying capacity when balanced with redeposition. Facilitating dissolution/redeposition promotes the formation of a disordered, cubic Zn‐rich phase, while the cathode that relies solely on Zn‐insertion forms a tetragonal ZnMn2 O4 phase.